Maternal hyperhomocysteinemia delays fetal brain maturation and leads to cognitive deficits - Baydas, G.; Koz, S. T.; Tuzcu, M.; Bulmus, O. (Blackwell Publishing, 2006)
[Abstract Not Available]
7th Biennial Meeting of the Asian-Pacific-Society-for-Neurochemistry -- JUL 02-05, 2006 -- Singapore, SINGAPORE